2009
DOI: 10.12806/v8/i1/ab2
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Leadership Development in the Classroom: A Narrative Approach

Abstract: This paper examines how a classroom designed process of constructing narratives about oneself, a group, and others helps students develop an authentic leadership voice. We begin by describing the theoretical framework behind our paper, which includes an overview of the notion of authenticity and the linkage between narrative and authentic leadership. Next, we provide an account of a transformative class called Leadership and Storytelling. Following this is a response to the question that inspired our paper: Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
(21 reference statements)
0
30
0
Order By: Relevance
“…McCormack, Illman, Culling, Ryan, and O'Neill (2002) suggested using a value clarification exercise and a visioning exercise in order to develop professional narratives. The work of Albert and Vadla (2009) is especially notable in this regard because it presents a coherent course plan. Based on their personal experience, the authors suggested giving written assignments to leadership students, aimed at evoking their emotional responses.…”
Section: Current Didactic Methods Of Authentic Leadership Developmentmentioning
confidence: 99%
“…McCormack, Illman, Culling, Ryan, and O'Neill (2002) suggested using a value clarification exercise and a visioning exercise in order to develop professional narratives. The work of Albert and Vadla (2009) is especially notable in this regard because it presents a coherent course plan. Based on their personal experience, the authors suggested giving written assignments to leadership students, aimed at evoking their emotional responses.…”
Section: Current Didactic Methods Of Authentic Leadership Developmentmentioning
confidence: 99%
“…For students to truly believe that the space is brave enough for their voices, the staff model vulnerability, describe their positionality, and exercise critical self‐reflection through their narratives. Adapting Albert and Vadla's () story assignments, staff members share their Who I Am and Who We Are stories with a focus on identifying stock and counter‐narratives in their lives. As educators, we have articulated nervousness and uncertainty in the creation and sharing of our narratives in front of our students.…”
Section: Practical Strategiesmentioning
confidence: 99%
“…Our experiences in and outside of traditional classroom learning environments demonstrate that it can take a while for students to understand that their narratives are worthy of examination. To assist in breaking through these normative assumptions, we emphasize the differentiation between storytelling and narrative which are often conflated both in the leadership literature and educational practice (Albert & Vadla, 2009). Boje (2001) clarified that "story is an account of incidents or events, but narrative comes after and adds 'plot' and 'coherence' to the story line" (Boje, 2001, p. 10).…”
Section: Defining Concepts: Narrativesmentioning
confidence: 99%
“…We analyse in particular the role of turning points (TP) in responsible leadership development, positing the TP acted as a mechanism in the development of leadership in corporate social responsibility (CSR). Furthermore, whilst TPs have been researched in developmental psychology (e.g., Gotlib and Wheaton 1997;McAdams et al 2001;Pillemer 2001) and to a limited extent in the leadership literature (e.g., Albert and Vadla 2009;Bennis and Thomas 2002;Janson 2008;Ligon et al 2008;Shamir and Eilam 2005), we further contribute to our understanding of this phenomenon by distinguishing the momentous turning point (MTP) in CSR leadership.…”
Section: Introductionmentioning
confidence: 96%